Penanganan Check-in Tamu Free Individual Traveller di Le Grande Bali Uluwatu - Fraciska, Ni Putu Erica Putri; Seniartha, I Wayan; Pitanatri, Made Uttari (Journal of Hospitality Accommodation Management (JHAM), 2024)
The purpose of this study is to analyze the handling of Free Individual Traveller guest check-in based on standard operating procedures. The number of samples in this study was 7 staff using interview and observation methods. Data collection is carried out using question assistance for resource persons, data is taken from resource persons who handle guest check-in, namely Guest Service Agent and Front Office manager, In addition, data collection was also carried out from observations of GSA regarding the handling of FIT guest check-in at Le Grande Hotel Bali Uluwatu. The data analysis technique used in this study is a qualitative descriptive research method based on Standard Operating Procedure in handling FIT guest check-in at Hote Le Grande Bali Uluwatu. The results of this study show that in general, the procedure for handling FIT guest check-in at Le Grande Bali Uluwatu Hotel is not in accordance with existing SOPs. It can be said that it is not suitable because Le Grande Bali Uluwatu Hotel expects 100% of these procedures to be implemented, while the percentage figure only reaches 70%. Based on the results of the study, suggestions that can be given are that Le Grande Bali Uluwatu hotels should deliver directions before work and after work so that they always apply standard operating procedures and awareness from guest service agents in implementing SOPs to support services at the hotel.